The universal enemy: Jihad, empire, and the challenge of solidarity - Li, Darryl (Stanford studies in Middle Eastern and Islamic societies and cultures, 2020)
No contemporary figure is more demonized than the Islamist foreign fighter who wages jihad around the world. Spreading violence, disregarding national borders, and rejecting secular norms, so-called jihadists seem opposed to universalism itself. In a radical departure from conventional wisdom on the topic, The Universal Enemy argues that transnational jihadists are engaged in their own form of universalism: these fighters struggle to realize an Islamist vision directed at all of humanity, transcending racial and cultural difference. Anthropologist and attorney Darryl Li reconceptualizes jihad as armed transnational solidarity under conditions of American empire, revisiting a pivotal moment after the Cold War when ethnic cleansing in the Balkans dominated global headlines. Muslim volunteers came from distant lands to fight in Bosnia-Herzegovina alongside their co-religionists, offering themselves as an alternative to the US-led international community. Li highlights the parallels and overlaps between transnational jihads and other universalisms such as the War on Terror, United Nations peacekeeping, and socialist Non-Alignment. Developed from more than a decade of research with former fighters in a half-dozen countries, The Universal Enemy explores the relationship between jihad and American empire to shed critical light on both.